THE LEGACY OF OLD ENGLISH LITERATURE IN MODERN ENGLISH CULTURE - Rozikova Zilola Tursunboy qizi; Jumaniyozova Xurshida Azimjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract This study investigates the lasting impact of Old English literature on modern English culture, emphasizing the ways in which early medieval texts continue to inform contemporary literature, language, and cultural understanding. Texts from the Anglo- Saxon period, including epic poems, religious compositions, and historical records, preserved the moral values and heroic ideals of their society while establishing the foundations for later English storytelling traditions. Through the analysis of works such as Beowulf, The Dream of the Rood, and early chronicles, the research highlights how themes like heroism, moral guidance, and stylistic features such as alliteration have been adapted and reinterpreted in subsequent English literary works. Additionally, the study examines the linguistic influence of Old English, including vocabulary, sentence structure, and expressive techniques, which continue to shape modern English writing. The research also underscores the importance of Old English literature in forming a sense of cultural identity, historical awareness, and literary continuity. Recognizing these contributions allows a deeper appreciation of the enduring legacy of early English literature in shaping contemporary literary and cultural landscapes.